2013
DOI: 10.1159/000355324
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course and Surgical Management of High Myopic Foveoschisis

Abstract: Purpose: To describe the spectral-domain optical coherence tomographic characteristics, natural course and surgical management for eyes with myopic foveoschisis. Methods: The medical records of 39 consecutive patients (56 eyes) with myopic foveoschisis were retrospectively reviewed. Pars plana vitrectomy with internal limiting membrane peeling and Brilliant Blue G staining was performed on 16 symptomatic eyes (14 patients). Results: Optical coherence tomography at baseline showed an isolated foveoschisis in 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…Vitrectomy surgery releases these intraocular forces. Rey et al 1 studied pars plana vitrectomy and internal limiting membrane peeling and also achieved good anatomical and functional results. Anatomical success was achieved in 75% of the eyes, with a mean follow-up period of 3.3 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Vitrectomy surgery releases these intraocular forces. Rey et al 1 studied pars plana vitrectomy and internal limiting membrane peeling and also achieved good anatomical and functional results. Anatomical success was achieved in 75% of the eyes, with a mean follow-up period of 3.3 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study reported full-thickness macular hole formation within a mean follow-up period of 15 months. 22 Another explanation may be found in a possible interaction between mCNV, continuous anti-VEGF treatment, and MRS.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity statistics show that 80%-90% of high school children are myopic in urbanized East Asia and that 10%-20% of them eventually develop high myopia [2, 3]. Among the myopic children, high myopia is the most worrying factor [4]. The most obvious characteristic of high myopia is gradual growth in axial length, which increases rapidly in childhood and adolescence and then grows out of control in adulthood [5].…”
Section: Introductionmentioning
confidence: 99%